Sugeno integral for Hermite-Hadamard inequality and quasi-arithmetic means - Nadhomi, Timothy (Annales Mathematicae Silesianae, 2023)
In this paper, we present the Sugeno integral of Hermite–Hadamard inequality for the case of quasi-arithmetically convex (q-ac) functions which acts as a generator for all quasi-arithmetic means in the frame work of Sugeno integral.